2006 Awards ceremony. - Illinois State Police. (Illinois State Police awards ceremony, 2006, 2006)
Contains summaries of incidents for which officers were rewarded.
Cover title.
Illinois State Police Department Awards Ceremony was held at the Illinois State Armory Building in Springfield, Illinois on May 3, 2006
Contains summaries of incidents for which officers were rewarded.
Keywords: Award presentations / Illinois.; Police, State / Illinois.